Diversity of Insects in Mangrove Ecosystem - Noor Farikhah Haneda; Cecep Kusmana; Fitria Dewi Kusuma (Jurnal Silvikultur Tropika, 2013)
Mangrove is the habitat of various insects which have important function of ecosystem. However, many insect species and their functions in mangrove ecosystem have not been identified yet. This research is aimed to elucidate the species composition of mangrove in relation to the species diversity of insect. This research was conducted in three different mangrove stand in Mangrove Protection Forest of Angke Kapuk and Soedyatmo highway mangrove area. They are monoculture stand of Avicennia marina, mixed stand of A. Marina and Rhizophora mucronata, and mixed stand of Sonneratia alba and R. mucronata. Sampling was collected by using line quadrat method. There were eight quadrats (10 m × 10 m) suspended at every mangrove stand. Incest traping was using yellow-pan trap method. The result indicates that the mixed stand A. Marina and R. mucronata has the highest value of insects abundance. The dominant insect at every mangrove stand were order of Diptera.